Pengaruh Bauran Pemasaran Jasa Terhadap Keputusan Pembelian Tiket Masuk Taman Rekreasi Sengkaling (Studi Kasus Pada Pengunjung Taman Rekreasi Sengkaling Malang)” - Moh Sholeh; N. Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT This study aims to test and analyze the Effect of Service Marketing Mix on Entrance Ticket Purchasing Decisions in Sengkaling Recreational Park both partially and jointly. Population and sample are all administrators totaling 80 people. Data collection through questionnaires. Data analysis in this study using SPSS version 17. The sampling technique using questionnaire distribution method and data testing techniques used in this study include validity test, reliability test, normality test, multiple linear regression analysis, and testing the research hypothesis. The results of the analysis show that partially the Service Marketing Mix has a significant effect on the Entrance Ticket Purchase Decision of Sengkaling Recreational Park, while jointly showing that the Service Marketing Mix has a significant effect on the Entrance Ticket Purchase of Sengkaling Recreational Park Keywords: Products, Prices, Promotions , Location, People, Physical Evidence, Process, Purchasing Decision